Copper (II) removal from aqueous solution using cobalt-doped iron oxide polyvinyl alcohol-alginate beads - Wong, Ee Ting (2015)
Copper (II) contaminated water threatens not only the aquatic lives but also human health due to the ability to accumulate in the food chains. Therefore, effective and economical technique must be developed to solve this issue. Although nanoparticles had been found effective in the removal of heavy metal and dye, theirs instability in aqueous solution had limited theirs practical usage. Therefore, in this research, the magnetic nanoparticles of cobalt-doped maghemite (Co-Fe2O3) which were synthesized by coprecipitation method using stable ferric and cobalt salts were immobilized in polyvinyl alcohol (PVA)-alginate matrix (in bead form) for the removal of copper (II). X-ray photoelectron spectroscopy (XPS) was then used to identify the copper (II) removal mechanism under photo condition. The effects of various parameters such as pH, catalyst dosage, light intensity and presence of negative organic compounds were investigated. After 180 min of sunlight irradiation exposure, copper (II) concentration was reduced to 1.080 ppm and 0.625 ppm at pH 4 and 6, respectively. This concentration complied with the World Health Organization (WHO) drinking water standard (less than 2.0 ppm). The optimum pH and catalyst dosage investigated were found to be pH 6 and 8% (v/v), respectively. In addition, organic additives like acetate and ethanol were found to enhance the copper (II) removal. The adsorption-desorption test further proved that Co-Fe2O3-PVA alginate bead has good recyclability with a drop of only 2.7% copper (II) removal efficiency after five cycles. Therefore, this bead is an attractive and ecofriendly separation tool to be applied in domestic water purification system under the sustainable light illumination.